2001
DOI: 10.1093/emboj/20.21.6158
|View full text |Cite
|
Sign up to set email alerts
|

DNA forms indicate rolling circle and recombination-dependent replication of Abutilon mosaic virus

Abstract: Geminiviruses have spread worldwide and have become increasingly important in crop plants during recent decades. Recombination among geminiviruses was one major source of new variants. Geminiviruses replicate via rolling circles, con®rmed here by electron microscopic visualization and two-dimensional gel analysis of Abutilon mosaic virus (AbMV) DNA. However, only a minority of DNA intermediates are consistent with this model. The majority are compatible with recombination-dependent replication (RDR). During de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
184
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(197 citation statements)
references
References 48 publications
8
184
1
4
Order By: Relevance
“…1b). As reported previously (Jeske et al, 2001), these signal smears bury the secrets of replicational dynamics, which can be unravelled by 2D electrophoresis (Figs 2 and 3). …”
supporting
confidence: 72%
See 3 more Smart Citations
“…1b). As reported previously (Jeske et al, 2001), these signal smears bury the secrets of replicational dynamics, which can be unravelled by 2D electrophoresis (Figs 2 and 3). …”
supporting
confidence: 72%
“…All of the MSV 2D blots showed clear evidence of RDR intermediates, indicated by faint arcs originating on dimeric cccDNA spots (labelled RDR in Figs 2 and 3). As described elsewhere (Jeske et al, 2001), similar intermediates originating on monomeric cccDNA spots could not be resolved in our 2D gels, because they are overprinted by the prominent tracks formed by the hdsDNA molecules that are produced as a result of RDR.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, a coupling between viral replication and recombination has been established for geminivirus (abutilon mosaic virus) infecting plant cells and agroinfection (Jeske et al, 2001). The authors concluded that the replication-dependent recombination (RDR) might indeed be a general replication process in this virus group.…”
Section: Introductionmentioning
confidence: 99%